The Internal Control Effort in Improving Company Performance - Hisar Pangaribuan; Jenny Sihombing; Denok Sunarsi; Daniel T.H. Manurung (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
The implementation of effective internal control contributes broadly to improving the implementation of corporate governance and performance. This study aims to confirm and describe how implementing effective internal control can improve company performance. Data were collected based on the respondents' perceptions, namely the internal control units of nine selected companies listed on the Indonesia Stock Exchange. A multiple regression approach processed the data. The test results proposed that the dimensions of internal control, namely monitoring activities, communication and information, control activities, risk assessment, and control environment, have a positive and significant influence on efforts to improve company performance. The board of commissioners must continue to direct and motivate management to implement effective internal control to improve company performance.